To solve this system of equations using substitution, we can solve for y in the first equation and then substitute that expression into the second equation.
From the first equation:
y = 12 + 9x
Now we substitute this into the second equation:
2x + 4(12 + 9x) = -28
2x + 48 + 36x = -28
38x + 48 = -28
38x = -76
x = -2
Now that we have found x, we can substitute it back into the first equation to find y:
-9(-2) + y = 12
18 + y = 12
y = -6
Therefore, the solution to the system of equations is (-2, -6).
Solving Equations Using Substitution Practice
Complete this assessment to review what you've learned. It will not count toward your grade.
4 of 54 of 5 Items
Question
Solve the system of equations.
–9x+y=12
2x+4y= −28(1 point)
(
,
)
Skip to navigation
1 answer